Peri and post-menopausal women with complex adnexal masses, ascites, and raised CA-125: Is it ovarian cancer or tuberculosis? - Rashmi Bagga; Tanuja Muthyala; Subhas Chandra Saha; Shalini Gainder; Pradip Kumar Saha; Radhika Srinivasan; Arvind Rajwanshi; Nalini Gupta (Wolters Kluwer Medknow Publications, 2016)
Pelvic and peritoneal tuberculosis may resemble advanced ovarian cancer due to the presence of ascites, complex adnexal masses, peritoneal deposits and raised CA-125 level, especially in peri- and postmenopausal women. Other common features among women with these two conditions are abdominal pain and distension, weight loss and reduced appetite. As the treatment of pelvic-peritoneal tuberculosis is completely different from that of ovarian cancer, it is important to reach a correct diagnosis. Sometimes women with pelvic-peritoneal tuberculosis may be subjected to a laparotomy for suspected ovarian cancer which is likely to increase their morbidity. In the present article, we report ten women in the peri- and post-menopausal age group where this diagnostic dilemma arose of whom seven were diagnosed only after a laparotomy had been performed for suspected ovarian cancer due to adnexal masses with ascites and raised CA-125 level. Ascitic fluid showing lymphocytic predominance, raised ADA level and absence of malignant cells are pointers to consider the possibility of pelvic- peritoneal tuberculosis, especially in endemic countries like India. In such situations, an effort should be made to obtain a cytological or histopathological diagnosis of either condition by ultrasound guided needle biopsy or laparoscopically obtained biopsy rather that proceeding with laparotomy for suspected ovarian cancer.